1990
DOI: 10.1121/1.399186
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional sound localization by human listeners

Abstract: This study measured the ability of subjects to localize broadband sound sources that varied in both horizontal and vertical location. Brief (150 ms) sounds were presented in a free field, and subjects reported the apparent stimulus location by turning to face the sound source; head orientation was measured electromagnetically. Localization of continuous sounds also was tested to estimate errors in the motor act of orienting with the head. Localization performance was excellent for brief sounds presented in fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
300
7
3

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 370 publications
(354 citation statements)
references
References 0 publications
44
300
7
3
Order By: Relevance
“…(It should be remembered here that, with the technique of measuring sound localization we used, both inconsistency in localization and systematic errors associated with specific regions of space can contribute to response variance.) Even with this degradation in performance, sound localization by blind-reared owls is good compared to the normal localization abilities of most other species, with the notable exception of humans (Makous and Middlebrooks, 1990). Thus, nonvisual sources of information can establish a reasonably good perception of auditory space without vision.…”
Section: Efects Of Blind Rearing On Sound Localizationmentioning
confidence: 90%
“…(It should be remembered here that, with the technique of measuring sound localization we used, both inconsistency in localization and systematic errors associated with specific regions of space can contribute to response variance.) Even with this degradation in performance, sound localization by blind-reared owls is good compared to the normal localization abilities of most other species, with the notable exception of humans (Makous and Middlebrooks, 1990). Thus, nonvisual sources of information can establish a reasonably good perception of auditory space without vision.…”
Section: Efects Of Blind Rearing On Sound Localizationmentioning
confidence: 90%
“…These observations suggest that PAF might have a principal role in sound localization. A difficulty with that argument is that populations of PAF neurons show their greatest location signaling accuracy for lateral regions of space, whereas psychophysical localization accuracy in cats (May and Huang, 1996;Tollin et al, 2005) and humans (e.g., Makous and Middlebrooks, 1990;Carlile et al, 1997) is greatest around the frontal midline. It might be that PAF scans regions that are remote from frontal attention, cooperating with another cortical field, such as DZ, to provide highacuity localization near the midline.…”
Section: Cortical Representation Of Sound Locationmentioning
confidence: 99%
“…(1) (Hartmann and Rakerd, 1989;Makous and Middlebrooks, 1990;Recanzone et al, 1998). Such comparisons could theoretically be valid if the assumptions typical to analyses of 2AFC tasks are satisfied, if data collected from absolute tasks accurately represent a subject's perceptual abilities, and that any effects arising from the disparities between tasks are inconsequential.…”
Section: Comparing Psychophysical Measures Of Acuity and Precisionmentioning
confidence: 99%
“…Unambiguous estimates of both accuracy and precision can be obtained from absolute paradigms but only a single measure of acuity, the MAA, is computed from relative tasks. It has frequently been inferred (e.g., Perrott, 1984;Perrott et al, 1987;Heffner and Heffner, 1992;Grantham et al, 2003), and occasionally directly suggested (Hartmann and Rakerd, 1989;Makous and Middlebrooks, 1990;Recanzone et al, 1998), that the MAA is specifically related to the precision of absolute sound localization estimates. In other words, the size of the MAA is singularly dependent upon the resolution with which a subject's auditory system computes directional cues, and therefore it conveys the consistency with which that observer could report the apparent location of sound sources in an absolute task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation